PENGARUH MEKANISME CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2007-2009) - Ririh Dian Pratiwi; Imam Gozali (MEDIA, 2012)
The purpose of this research is to examine the influence of the corporate governance mechanism to the firm value. The variables examined in this research are audit committe (audit committee activity and expertise of audit committee), board of commissioner (board of commissioner activity and independent commissioner), institutional ownership, managerial ownershipÂ  and firm value. The sample which used in this research are manufacturing companies listed at Indonesian Stock Exchange on period of 2007-2009. This research is using purposive sampling method to determine the sample and resulted 44 companies as research sample. Multiple regression model and statistic descriptive is used to analysis data. The result of this research shows the corporate governance mechanism (expertise of audit committee, independent commissioner and managerial ownership) had positive effect and significant to firm value. Audit committee activity, board of commissioner activity, and Institutional ownership are not influence to firm value.